Analisis Digitalisasi Pada Metode Pembayaran Di Koperasi Peternakan XYZ - Rosaria, Ranita; Christian Wiradendi Wolor; Eka Dewi Utari (Indonesian Journal Publisher, 2025)
This research aims to analyze the potential of QRIS (Quick Response Code Indonesian Standard) based digital payment system implementation in XYZ Farming Cooperative. The objectives of this study include mapping the payment system currently used, identifying barriers in the digitization process, and projecting the impact of QRIS implementation on transaction efficiency and operational sustainability of the cooperative. The research method used is descriptive analysis with a qualitative approach, through data collection using open-ended questionnaires and in-depth interviews with cooperative members and management. The background of this research is based on the need to improve efficiency and effectiveness in the cooperative payment system through the adoption of digital technology. The results show that transactions in XYZ Farming Cooperative are still dominated by cash payments, which are considered less efficient by most respondents in the pre-research questionnaire. Meanwhile, the implementation of QRIS is considered to have great potential to support cooperative operations in a more practical and modern manner, despite the challenges of low digital literacy and limited infrastructure. This research recommends increasing the digital capacity of cooperative members through training, provision of technological facilities, and gradual implementation of non-cash payment system trials.